IMPORTANCE OF FLORA PAINTINGS IN INDIAN ART AND MYTHOLOGY - Faizullah Ahmad; Badar Jahan (International Journal of Research -GRANTHAALAYAH, 2025)
Since ancient times, India has had a tradition of worshipping objects that serve its needs, evidenced in the Vedas and Puranas, and their significance in our lives has been written and painted in many books, texts, and on walls. This research paper discusses flora paintings and their relevance in Indian art and mythology. Indian art is known for its rich tradition of depicting nature. Flora in Indian art is a medium to express the interrelationship of the divine and natural world. Through flora paintings, artists depict the sanctity of nature, drawing inspiration from ancient texts, folklore and religious traditions. Many trees, plants, flowers, mountains, and rivers symbolize fertility and wisdom. In mythology, flora has symbolic significance, representing deities and cosmic forces. How artists from different groups and periods have captured the essence of the natural world through brushstrokes and vibrant colors invites contemplation on the interconnectedness of all living beings. The researcher using secondary data and descriptive research methodology, this paper re-examines the role of flora painting in promoting societal expression and needs. Finally, the paper presents a detailed analysis of how different regions depict flora in the context of their local myths and religious beliefs and highlights the diversity and richness of Indian art.